Legal Position of Employment Agreement after the Enactment of Government Regulation in Lieu of Law (Perpu) Number 02 of 2022 Concerning Manpower - Pandora Manalu, Evanto; Hajati Hoesin, Siti; Bangun Pandapotan Hutajulu; Rinaldi Agusta Fahlevie (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
The government has replaced Law Number 2 of 2022 on Job Creation, eliminating derivative provisions from Law Number 11 of 2020 on Employment and citing the principles of Legal Certainty and Protection. The terms of employment contracts are predominantly governed by Law Number 13 of 2003 on Manpower, with specific provisions from Law Number 11 of 2020 remaining intact, such as the conversion from Fixed-Term Work Agreements/ Perjanjian Kerja Waktu Tertentu (PKWT) to Permanent Work Agreements/Perjanjian Kerja Waktu Tertentu (PKWTT). Meanwhile, Government Regulation Number 35 of 2021 has been rescinded by the newly implemented Regulation, posing challenges for legal status adjustments in district courts. This investigation aims to scrutinize and elucidate the execution of converting PKWT to PKWTT before enacting the Government Regulation in Lieu of Law (Perppu) and the Omnibus Law. Subsequently, the aim is to explore and clarify the conversion of fixed-term work contracts such as PKWT into permanent work contracts such as PKWTT following the implementation of the Perppu. This study adopts a normative/doctrinal approach. The consulted literature encompasses various legal documents, including Government Regulation Number 35 of 2021. Then, it was found that the significance of regulations concerning the PKWT to PKWTT conversion was underscored in offering clarity to workers in their daily tasks. The Manpower Law imposes restrictions on work agreements with employees, mandating written contracts in Indonesian and prohibiting multiple extensions beyond the stipulated limit.